Dialética dos sentidos de trabalho pedagógico para os professores de Educação Física da rede municipal de ensino de Santa Maria/RS - Dalla Nora, Daiane (2021)
This thesis is part of Research Line 2 - Public Policies, Educational Practices and their Interfaces of the Graduate Program in Education and is integrated with the research developed by KAIRÓS - Study and Research Group on Work, Education and Policies Public. The proposal arises from the academic debate of the Group, in the last decade, about the work of teachers, being understood as pedagogical work. The research sought to problematize the meanings of pedagogical work for teachers. As a general objective, it was established to analyze, from the speeches, the meanings of pedagogical work attributed by Physical Education teachers of the Municipal Teaching Network of Santa Maria / RS and, as they contribute to the configuration of a context of dialectic of the work senses pedagogical. As specific objectives: characterize the organization of Physical Education in RMESM; to analyze how pedagogical work is characterized, the challenges and the possibilities, considering the reality of PE teachers; understand how teachers become teachers and the movement of producing the meanings of pedagogical work; categorize and analyze the meanings of pedagogical work for PE teachers based on the dialectic of the senses; describe the movement of the dialectic of the senses of pedagogical work and the processes related to the work of PE teachers. There were methodological procedures: the Questionnaire, the Documentary Research and the Semi-structured Interview. The analysis of the data produced was carried out by dialectical analysis, from the categories: totality, historicity, contradiction, mediation and praxis. It was verified the existence of a dialectical relationship between pedagogical work and senses, so that an intentional, naive and provisional/strategic pedagogical work produces, respectively, intentional, naive and provisional/strategic sense, from the phenomenon of the dialectic of the senses of pedagogical work.